LINGUOPRAGMATIC PECULIARITIES OF ENGLISH YOUTH SLANG ACROSS GENERATIONS X, Y, Z, AND ALPH - Khamzaev Sobir Amirovich; Mamasalieva Zulfiya (World Scientific Research Journal, 2025)
Abstract: This article explores the linguopragmatic peculiarities of English youth slang and its evolution across Generations X, Y, Z, and Alpha. Youth slang serves as a dynamic linguistic phenomenon reflecting societal changes, technological advancements, and cultural shifts. The study highlights key characteristics of each generational slang, including semantic innovation, pragmatic function, and digital influence. Understanding these variations provides insights into intergenerational communication and language evolution